2019
DOI: 10.5483/bmbrep.2019.52.3.146
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress causes Alu RNA accumulation via PIWIL4 sequestration into stress granules

Abstract: The Alu element, the most abundant transposable element, is transcribed to Alu RNA. We hypothesized that the PIWI protein regulates the expression of Alu RNA in retinal pigment epithelial (RPE) cells, where accumulated Alu RNA leads to macular degeneration. Alu transcription was induced in RPE cells treated with H 2 O 2 . At an early stage of oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…An increase in C3aR protein expression 24 h after treatment, as shown at the mRNA level, could not be veri ed. This might be explained by storage of C3AR RNA into RNA granules, either stress granules or processing bodies (41). ARPE-19 cells express the α-chain CD11b of the integrin complement receptor CR3 (30).…”
Section: Fhr-3 Increased Endogenous Complement Activationmentioning
confidence: 99%
“…An increase in C3aR protein expression 24 h after treatment, as shown at the mRNA level, could not be veri ed. This might be explained by storage of C3AR RNA into RNA granules, either stress granules or processing bodies (41). ARPE-19 cells express the α-chain CD11b of the integrin complement receptor CR3 (30).…”
Section: Fhr-3 Increased Endogenous Complement Activationmentioning
confidence: 99%
“…Free Alu transcripts are expressed at very low levels in physiological conditions, approximately only 10 2 -10 3 molecules per cell; while the levels increases under various stresses, such as heat shock (Pandey et al, 2011), hyperglycemia (Wang et al, 2016) and viral infection (Panning and Smiley, 1994). It's been reported that Alu RNA accumulation induces ROS production and impedes SOD2 expression in cells while higher oxidative stress leads to more severe Alu RNA accumulation (Wang et al, 2016;Hwang et al, 2019). Kaneko et al (2011) found that deficiency of Dicer1, an RNase III involved in microRNA biogenesis (Bernstein et al, 2001), leads to cytotoxic Alu RNA accumulation in human RPE cells and RPE degeneration in mice shown by Fundus examination and RPE/choroid flat mount.…”
Section: Alu Rnamentioning
confidence: 99%
“…Alu is the most abundant transposable element, which is transcribed into Alu RNAs, and the accumulation of Alu RNAs has been confirmed to be related to AMD [76]. Alu RNAs, by reducing DICER1, can activate the inflammasome in RPE cells and increase IL-18 levels, leading to geographic atrophy.…”
Section: Abnormal Immune-inflammatory Responses Are Pathogenic Facmentioning
confidence: 99%